2018
DOI: 10.4034/pboci.2018.181.05
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Preventive Methods Applied to the Occlusal Surface of Primary Teeth: A Randomized Clinical Study

Abstract: Objective: To evaluate the clinical performance of three preventive materials on the occlusal surfaces of primary molars over a 36-month period. Material and Methods: The study was conducted with a split-mouth design involving four experimental groups: G1 -resin-modified glass ionomer cement (Vitremer ® ); G2 -resin sealant (Alpha Seal Light ® ); G3 -silver diamine fluoride (Cariostatic ® ); and G4 -control group without material. Thirty-two children aged 36 to 60 months, attending a pediatric clinic, with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In Brazil, 38% of SDF is available on the market only associated with KI. Considering the present study, it was also observed that the 10% concentration was used only in enamel [36,37]. In comparison, the 12% SDF was only used in studies comparing this concentration with 38%, and it was not as effective as 38% in arrest dentin caries lesions [22,23,38].…”
Section: Discussionmentioning
confidence: 58%
“…In Brazil, 38% of SDF is available on the market only associated with KI. Considering the present study, it was also observed that the 10% concentration was used only in enamel [36,37]. In comparison, the 12% SDF was only used in studies comparing this concentration with 38%, and it was not as effective as 38% in arrest dentin caries lesions [22,23,38].…”
Section: Discussionmentioning
confidence: 58%
“…The Food and Drug Administration approved it in 2014 as a desensitizing agent, and since then, its use and research interest have increased both in the US and, more recently, in Europe [113][114][115][116].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for standardization of data presentation in RCTs evaluating caries arrest. On literature review, studies comparing SDF and ART on non-carious first permanent molars were excluded[ 18 19 ]; and since only one study[ 16 ] was included in the qualitative review, the data on first permanent molars could not be meta-analyzed. It is important to emphasize that the included split-mouth RCT in permanent molars[ 16 ] does not ensure intervention fidelity as chances of a possible carryover effect between different treatment groups cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%